Thin-wall porous ceramic material and preparation method thereof

By ball milling-sieving and surface modification of silicon carbide honeycomb ceramic waste, thin-walled porous ceramic materials suitable for National VII emission regulations were prepared, which solved the problem of resource waste and difficult to reduce material costs, and achieved low-cost and high-efficiency ceramic materials preparation.

CN119735427APending Publication Date: 2025-04-01SHANDONG AOFU ENVIRONMENTAL PROTECTION SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510245146.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art fails to effectively utilize silicon carbide honeycomb ceramic waste, resulting in waste of resources and difficult to reduce material costs.

Method used

Silicon carbide honeycomb ceramic waste is used to prepare thin-walled porous ceramic materials, and ceramic materials with low cost and high efficiency are prepared by ball milling-sieving and surface modification of clinker.

Benefits of technology

The effective recycling of silicon carbide honeycomb ceramic solid waste was achieved, production costs were reduced, and thin-walled porous ceramic materials suitable for National VII emission regulations were prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735427A_ABST
    Figure CN119735427A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of honeycomb ceramics, in particular to a thin-wall porous ceramic material and a preparation method thereof. The method is prepared from silicon carbide honeycomb ceramic waste. The silicon carbide honeycomb ceramic waste comprises clinker and / or raw material, the clinker is waste which is sintered and not subjected to cold processing, and the raw material is waste which is not sintered; the preparation method comprises the step of pretreating the clinker and / or the raw material, and the pretreatment step comprises the step of carrying out ball milling-screening and surface modification treatment on the clinker to obtain clinker powder; the particle size D50 of the clinker powder is 10-30 [mu] m, and the particle size D100 is less than 100 [mu] m. According to the method, effective circulation and high-efficiency utilization of the silicon carbide honeycomb ceramic solid waste are realized; the thin-wall porous ceramic material is low in cost, high in efficiency and suitable for national VII emission regulations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of honeycomb ceramics, and in particular to a thin-wall porous ceramic material and a preparation method thereof. Background Art

[0002] At present, increasingly stringent emission regulations have been issued and implemented. The National VI emission regulations are becoming more and more perfect, and the new National VII emission national standard is about to be implemented, which puts forward more stringent requirements on the performance and use performance of ceramic materials of diesel vehicle particulate filters. Among the diesel vehicle filters used in the National VI regulation stage, the market share of honeycomb ceramic filters made of silicon carbide has increased significantly. As a domestic emerging material in the field of honeycomb ceramics, silicon carbide ceramics can still produce large-scale raw materials and / or ceramic clinker bulk solid waste materials during the production and preparation process. For porous ceramics made of silicon carbide, its high-temperature strength can be maintained above 1600°C. The clinker solid waste materials generated in the preparation process of the National VI honeycomb ceramic filter retain the excellent properties of the original ceramic material and do not damage the crystal structure of the ceramic material. The raw solid waste materials generated are more suitable for re-matching and sintering.

[0003] In the prior art, there is no effective solution for the utilization of waste materials, which results in waste of waste materials and makes it difficult to reduce the cost of honeycomb ceramic materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a thin-wall porous ceramic material and a preparation method thereof.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: The present invention provides a method for preparing a thin-walled porous ceramic material, characterized in that the thin-walled porous ceramic material is prepared by using silicon carbide honeycomb ceramic waste; the silicon carbide honeycomb ceramic waste includes clinker and / or raw material, the clinker is waste material that has been sintered but not cold-processed, and the raw material is waste material that has not been sintered; The preparation method comprises the step of pre-treating the clinker and / or the raw material, wherein the pre-treating step comprises ball milling-sieving and surface modification of the clinker to obtain clinker powder; the particle size of the clinker powder is D 50 10-30μm, particle size D 100 Less than 100μm.

[0006] Based on the above technical solution, the present invention can also be improved as follows.

[0007] Furthermore, the pretreatment step also includes dissolving the raw material in water.

[0008] Furthermore, the sintering method of the clinker includes sintering in a reducing protective atmosphere or sintering in an oxidizing atmosphere.

[0009] Furthermore, the surface modification treatment is a chemical coating modification treatment using a chemical modifier, and the chemical modifier is one or more of an organic silane coupling agent, a titanate coupling agent, an aluminate coupling agent, an organic complex, organic silicon, and PEI.

[0010] Further, the following steps are included: S1, pre-treating the clinker and / or the raw material; S2, obtaining a first mixed powder or a second mixed powder, wherein the first mixed powder is a mixture of alumina powder, inorganic gel powder, pore former, organic binder and the pretreated clinker, and the second mixed powder is a mixture of alumina powder, inorganic gel powder, pore former and organic binder; S3, mixing the first mixed powder with the pretreated raw material to obtain a kneading material, or mixing the second mixed powder with the pretreated raw material to obtain a kneading material; wet kneading the kneading material with a lubricant and water to obtain a mud material; the lubricant includes a waste oil-water mixture and / or an organic lubricating dispersant; S4, preparing and cutting the clay material to obtain clay segments; S5, removing coarse particles with a particle size greater than 100 μm in the mud section, and then performing extrusion molding, microwave, drying and sintering to obtain the thin-walled porous ceramic material.

[0011] Further, in step S2, based on the total mass of the clinker and the raw material as 100%, the mass percentage of the alumina powder is 7%-9%, the mass percentage of the inorganic gel powder is 7%-9%, the mass percentage of the pore former is 36%-40%, and the mass percentage of the organic binder is 8%-12%.

[0012] Furthermore, the organic binder is one or more of cellulose, polyvinyl alcohol, and nylon plastic, and the pore-forming agent is one or more of starch pore-forming agent, polymethyl methacrylate, and resin pore-forming agent.

[0013] Furthermore, in step S3, based on the total mass of the kneaded material being 100%, the mass percentage of the lubricant is 13%-15%, and the mass percentage of water is 4%-8%.

[0014] Further, in step S5, the sintering method is consistent with the sintering method of the clinker.

[0015] The present invention also provides a thin-wall porous ceramic material, which is prepared by the above-mentioned preparation method.

[0016] The beneficial effects of the present invention are: (1) The method for preparing the thin-walled porous ceramic material of the present invention uses silicon carbide honeycomb ceramic waste as raw material, and performs ball milling-screening and surface modification treatment on the clinker therein, thereby achieving effective recycling and high-efficiency utilization of silicon carbide honeycomb ceramic solid waste; (2) The method for preparing the thin-walled porous ceramic material of the present invention has low cost and high efficiency, and is applicable to the National VII emission regulations; (3) The thin-walled porous ceramic material of the present invention, wherein the wall thickness / pore density can reach the specific specifications of 3-7 mil / 300-600 cpsi, and meets the applicability of ceramic products to the National VII emission regulations; (4) The thin-walled porous ceramic material of the present invention has good anti-oxidation performance and a high softening temperature, and can fully meet the working conditions of less than or equal to 1500°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The method for preparing the thin-walled porous ceramic material of the present invention is a SEM image of silicon carbide clinker powder after surface shaping treatment; Figure 2 The present invention is a method for preparing a thin-walled porous ceramic material, and a schematic diagram of a pretreatment process of a clinker; Figure 3 The method for preparing the thin-walled porous ceramic material of the present invention, the SEM micrograph of the surface of the thin-walled porous ceramic material in Example 4; Figure 4 The method for preparing the thin-walled porous ceramic material of the present invention, the SEM micrograph of the wall surface of the thin-walled porous ceramic material in Example 4; Figure 5 It is a schematic flow chart of the method for preparing the thin-walled porous ceramic material of the present invention; Figure 6 The SEM comparison diagram of the thin-walled porous ceramic material of the present invention, the thin-walled porous ceramic material in Example 4, before and after calcination at 1500°C / 100H, Figure 6 A in the middle is before burning, Figure 6 B in the middle is after burning. DETAILED DESCRIPTION

[0018] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0019] The preparation method of the thin-walled porous ceramic material of the present invention adopts silicon carbide honeycomb ceramic waste to prepare the material; the silicon carbide honeycomb ceramic waste includes clinker and / or raw material, the clinker is the waste material that has been sintered but not cold processed, and the raw material is the waste material that has not been sintered; the preparation method includes the step of pretreating the clinker and / or raw material, the pretreating step includes ball milling-sieving and surface modification treatment of the clinker to obtain clinker powder; the particle size D of the clinker powder 50 10-30μm, particle size D 100 Less than 100μm.

[0020] The preparation method of the thin-walled porous ceramic material of the present invention adopts silicon carbide honeycomb ceramic waste as raw material, and performs ball milling-screening and surface modification treatment on the clinker therein, thereby realizing the effective circulation and high-efficiency utilization of silicon carbide honeycomb ceramic solid waste, and the obtained thin-walled porous ceramic material has low cost and high efficiency, and is applicable to the National VII emission regulations.

[0021] Regarding the particle size of the clinker powder, when the particle size is too large, it will lead to failure in extrusion and cannot meet the requirements for preparing thin-walled porous materials. When the particle size is too small, although thin-walled porous materials can be prepared, the preparation cost of the clinker powder is increased.

[0022] It should be noted that in silicon carbide honeycomb ceramic waste, raw materials include raw material powder and mud material waste. Raw material powder is a solid waste material with rib wall defects or microwave defects in the production process. It is a semi-finished product that has been extruded but not fired. Mud material waste is a semi-finished product after the mud kneading process but before the extrusion process. Clinker is a semi-finished product that has been fired but not cold processed.

[0023] In a certain embodiment of the present invention, the SEM image of the silicon carbide clinker powder after surface shaping treatment is as follows: Figure 1 shown.

[0024] Since the clinker and raw material used in the present invention are both silicon carbide honeycomb ceramic waste, the material thereof is known, and the specific chemical composition has no substantial influence on the preparation method and effect of the present invention.

[0025] Preferably, the main crystal phase of the clinker can be 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide; it can also be 60%-80% silicon carbide, 20-30% cristobalite, and 5-10% of a small amount of oxide crystal phases such as cordierite.

[0026] Preferably, the raw material components of the raw material and the clinker can be the same or different.

[0027] In addition, since clinker is waste material after sintering, and the sintering process has a certain influence on the properties of clinker, therefore, when reusing clinker, it is necessary to determine the sintering method of clinker, and in the process of making new thin-walled porous ceramic materials, it is necessary to ensure that the sintering method is consistent with the sintering method of clinker, so as to ensure the performance of the newly prepared porous ceramic material.

[0028] Preferably, the clinker is sintered in a reducing protective atmosphere or in an oxidizing atmosphere.

[0029] Preferably, the surface modification of the clinker is a chemical coating modification treatment using a chemical modifier, wherein the chemical modifier is one or more of an organic silane coupling agent, a titanate coupling agent, an aluminate coupling agent, an organic complex, an organic silicon, and PEI; through the chemical coating modification treatment, a coating layer is formed on the surface of the powder particles of the clinker, thereby effectively improving the electrostatic repulsion on the surface of the powder particles of the clinker, and improving the dispersibility and fluidity of the powder particles of the clinker.

[0030] Preferably, the pretreatment step further comprises dissolving the raw material in water.

[0031] The preparation method of the present invention has no specific restrictions on the mass percentage of raw materials and clinker. When only raw materials are used without clinker, the porosity, pore size, compressive strength, softening temperature and oxidation resistance of the thin-walled porous ceramic material also meet the standards. Although the thin-walled porous ceramic material cannot be formed when only clinker is used without raw materials, In order to meet the requirements of low cost and high efficiency at the same time, preferably, the ratio of clinker to raw material is 4:6. Although excessive use of clinker or excessive use of raw material based on this ratio will cause the product softening temperature or cost to be too high, it still falls within the scope of protection of the present invention.

[0032] The preparation method of the present invention specifically comprises the following steps: S1. Pre-treat clinker and / or raw material.

[0033] Preferably, the clinker is ball-milled, and then sieved to obtain a powder with a mesh size of 500 or more, and then subjected to surface modification treatment to obtain clinker powder. The ball-milling time is 4 hours.

[0034] S2, obtaining a first mixed powder or a second mixed powder, wherein the first mixed powder is a mixture of alumina powder, inorganic gel powder, pore former, organic binder and pretreated clinker, and the second mixed powder is a mixture of alumina powder, inorganic gel powder, pore former and organic binder; Preferably, based on the total mass of the clinker and the raw material as 100%, the mass percentage of the alumina powder is 7%-9%, the mass percentage of the inorganic gel powder is 7%-9%, the mass percentage of the pore former is 36%-40%, and the mass percentage of the organic binder is 8%-12%.

[0035] Preferably, the organic binder is one or more of cellulose, polyvinyl alcohol, and nylon plastic, and the pore-forming agent is one or more of starch pore-forming agent, polymethyl methacrylate, and resin pore-forming agent.

[0036] Inorganic gel powder is a clay-based inorganic raw material, the main components of which are silicon oxide, aluminum oxide, magnesium oxide and a small amount of impurities. The mass percentage of impurities is generally less than 1.5%, and the impurities may be iron, titanium, potassium, sodium, calcium, etc.

[0037] S3. Mix the first mixed powder with the pretreated raw material to obtain a kneaded material, or mix the second mixed powder with the pretreated raw material to obtain a kneaded material; wet-knead the kneaded material with a lubricant and water to obtain a mud material; the lubricant includes a waste oil-water mixture and an organic lubricating dispersant; this step can further adjust the packaging and extrusion molding process of raw / cooked waste.

[0038] The lubricant used in this step can be the waste oil-water mixture produced during the microwave stage of the raw material. Experimental verification shows that the dispersibility and lubricity of the waste meet the process requirements of mud extrusion molding, and it can effectively replace organic lubricating dispersants and realize the recycling and reuse of waste.

[0039] Since it is a recycling of waste materials, when the material properties of the existing mud are not sufficient to meet the requirements of the extrusion process, an organic lubricating dispersant can be used to supplement the lubricity; organic lubricating dispersants include but are not limited to soybean oil or butter.

[0040] Preferably, based on the total mass of the kneaded material being 100%, the mass percentage of the lubricant is 13%-15%, and the mass percentage of water is 4%-8%.

[0041] Preferably, the organic lubricating dispersant is soybean oil or butter.

[0042] Preferably, when the lubricant contains an organic lubricating dispersant, the mass ratio of the waste oil-water mixture to the organic lubricating dispersant is 28:1.

[0043] S4, training and cutting the clay material to obtain clay segments.

[0044] S5, removing coarse particles with a particle size greater than 100 μm in the mud section, and then performing extrusion molding, microwave, drying and sintering to obtain the thin-walled porous ceramic material.

[0045] Preferably, in this step, the mud segment is screened by a hydraulic high-pressure screening machine with a high-mesh screen.

[0046] Preferably, the pressure of the hydraulic high-pressure screening machine is 20 MPa.

[0047] The sintering method in this step is consistent with the sintering method of clinker, and the sintering process is a conventional sintering step.

[0048] Preferably, the sintering process is: First, debind and sinter in an oxidation furnace at 400-700℃ to remove organic matter from the product.

[0049] When sintering in a reducing protective atmosphere, the sintering temperature is adjusted to 1400-1700°C in a vacuum environment that can be filled with inert gas. During the sintering process, the metal silicon melts and wraps around the silicon carbide particles to form a product with high bonding strength and qualified appearance.

[0050] When sintering in an oxidizing atmosphere, an oxidation pretreatment sintering is performed at 1100-1500°C in an oxidation furnace to form a dense SiO2 protective film.

[0051] The preparation method of the present invention uses silicon carbide honeycomb ceramic waste as the main raw material, realizes high-efficiency recycling of solid waste, reduces the production cost of the enterprise, and prepares thin-walled porous ceramic materials.

[0052] It should be pointed out in particular that for waste materials such as clay / raw materials / cooked materials of ceramic products with different sintering processes, the raw material ratio of the new formula should be calculated according to the different material components, and the new formula should be sintered according to the original established sintering process to obtain thin-walled porous ceramic products with performance that meets the requirements.

[0053] The thin-wall porous ceramic material of the present invention is prepared by the above-mentioned preparation method.

[0054] The thin-walled porous ceramic material of the present invention can reach the specific specifications of wall thickness / pore density of 3-7 mil / 300-600 cpsi, and meet the applicability of ceramic products to the National VII emission regulations. It has good antioxidant properties and a high softening temperature, and can fully meet the working conditions of less than or equal to 1500°C.

[0055] The present invention is illustrated below by means of specific examples.

[0056] Example 1 like Figure 2As shown in the figure, the preparation process of the clinker powder in this embodiment is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 4 hours. After ball milling, the powder with a mesh size of 400-500 is sieved. After testing, the particle size D of the powder is 50 10-30μm, particle size D 100 Less than 100μm.

[0057] The clinker of this embodiment is sintered in a reducing atmosphere and a protective atmosphere. The main crystal phases of the clinker and the raw material of this embodiment are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0058] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0059] The preparation process of the thin-walled porous ceramic material of this embodiment is as follows: (1) 50% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore former, and 10% by weight of an organic binder are mixed by a dry method to obtain a densely packed and uniform mixed powder.

[0060] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0061] (2) The mixed powder is placed in a kneading machine, and then 50% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total weight of the mixed powder and the raw meal being 100%, the weight percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the weight percentage of water is 6%.

[0062] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0063] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0064] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0065] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0066] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0067] (7) Detect the properties of the prepared porous ceramic materials.

[0068] Example 2 like Figure 2 As shown in the figure, the preparation process of the clinker powder in this embodiment is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 4 hours. After ball milling, the powder with a mesh size of 400-500 is sieved. After testing, the particle size D of the powder is 50 10-30μm, particle size D 100 Less than 100μm.

[0069] The clinker of this embodiment is sintered in a reducing atmosphere and a protective atmosphere. The main crystal phases of the clinker and the raw material of this embodiment are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0070] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0071] The preparation process of the thin-walled porous ceramic material of this embodiment is as follows: (1) 70% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore former, and 10% by weight of an organic binder are mixed by a dry method to prepare a mixed powder having a dense and uniform structure.

[0072] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0073] (2) The mixed powder is placed in a kneading machine, and then 30% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total mass of the mixed powder and the raw meal being 100%, the mass percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the mass percentage of water is 6%.

[0074] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0075] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0076] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0077] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0078] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0079] (7) Detect the properties of the prepared porous ceramic materials.

[0080] Example 3 like Figure 2 As shown in the figure, the preparation process of the clinker powder in this embodiment is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 4 hours. After ball milling, the powder with a mesh size of 400-500 is sieved. After testing, the particle size D of the powder is 50 10-30μm, particle size D 100 Less than 100μm.

[0081] The clinker of this embodiment is sintered in a reducing atmosphere and a protective atmosphere. The main crystal phases of the clinker and the raw material of this embodiment are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0082] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0083] The preparation process of the thin-walled porous ceramic material of this embodiment is as follows: (1) 30% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore-forming agent, and 10% by weight of an organic binder are mixed by a dry method to obtain a densely packed and uniform mixed powder.

[0084] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0085] (2) The mixed powder is placed in a kneading machine, and then 70% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total mass of the mixed powder and the raw meal being 100%, the mass percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the mass percentage of water is 6%.

[0086] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0087] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0088] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0089] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0090] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0091] (7) Detect the properties of the prepared porous ceramic materials.

[0092] Example 4 like Figure 2 As shown in the figure, the preparation process of the clinker powder in this embodiment is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 4 hours. After ball milling, the powder with a mesh size of 400-500 is sieved. After testing, the particle size D of the powder is 50 10-30μm, particle size D 100 Less than 100μm.

[0093] The clinker of this embodiment is sintered in a reducing atmosphere and a protective atmosphere. The main crystal phases of the clinker and the raw material of this embodiment are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0094] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0095] The preparation process of the thin-walled porous ceramic material of this embodiment is as follows: (1) 40% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore-forming agent, and 10% by weight of an organic binder are mixed by a dry method to obtain a densely packed and uniform mixed powder.

[0096] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0097] (2) The mixed powder is placed in a kneading machine, and then 60% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total mass of the mixed powder and the raw meal being 100%, the mass percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the mass percentage of water is 6%.

[0098] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0099] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0100] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0101] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0102] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0103] (7) Detect the properties of the prepared porous ceramic materials.

[0104] Example 5 This embodiment does not use clinker, and the main crystal phases of the raw material of this embodiment are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0105] The preparation process of the thin-walled porous ceramic material of this embodiment is as follows: (1) A closely packed and uniform mixed powder is prepared by dry mixing 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore former, and 10% by weight of an organic binder.

[0106] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0107] (2) The mixed powder is placed in a kneading machine, and then 100% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and the mixture is kneaded to obtain a slurry. Wherein, based on the total mass of the mixed powder and the raw meal being 100%, the mass percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the mass percentage of water is 6%.

[0108] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0109] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0110] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0111] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0112] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0113] (7) Detect the properties of the prepared porous ceramic materials.

[0114] Example 6 like Figure 2 As shown in the figure, the preparation process of the clinker powder in this embodiment is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 4 hours. After ball milling, the powder with a mesh size of 400-500 is sieved. After testing, the particle size D of the powder is 5010-30μm, particle size D 100 Less than 100μm.

[0115] The clinker of this embodiment is sintered in an oxidizing atmosphere. The main crystal phases of the clinker and raw material of this embodiment are 60%-80% silicon carbide, 20-30% cristobalite, and 5-10% cordierite crystal phases.

[0116] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0117] The preparation process of the thin-walled porous ceramic material of this embodiment is as follows: (1) 40% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore-forming agent, and 10% by weight of an organic binder are mixed by a dry method to obtain a densely packed and uniform mixed powder.

[0118] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0119] (2) The mixed powder is placed in a kneading machine, and then 60% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total mass of the mixed powder and the raw meal being 100%, the mass percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the mass percentage of water is 6%.

[0120] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0121] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0122] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0123] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0124] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0125] (7) Detect the properties of the prepared porous ceramic materials.

[0126] Comparative Example 1 (1) Dry-mix 75% by weight of 25-28 μm silicon carbide powder and 25% by weight of 3-6 μm metal silicon. Add 48% by weight of 20-25 μm foaming resin and 9% by weight of organic binder to the total weight of the inorganic material to obtain a uniform mixture with tight packing. The amount of binder and pore-forming agent added is based on the amount of inorganic material, and the binder is hydroxypropyl methylcellulose.

[0127] (2) The mixed powder is placed in a kneading machine, and 15% by weight of water, 3% by weight of acidic silica sol, and 4% by weight of acidic aluminum sol are added and kneaded for 17 minutes.

[0128] 1.0% by weight of lubricant and 1% by weight of dispersant were added and kneaded for 17-34 minutes. The addition amount of the two was based on the total mixed powder component, and the purpose was to increase the plasticity, lubricity and surface activity of the mud. The organic lubricating dispersant in this comparative example was butter.

[0129] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0130] (4) In this comparative example, the plastic clay segment was extruded into a honeycomb structure, and a green body with a size of 40×40×189 mm was extruded with an outer skin, and then microwaved and dried.

[0131] (5) After the dried blank is cut into a fixed height of 177.8 mm, a laser drilling-hole plugging process is performed with a plugging depth of 8-10 mm. The square holes of the product are processed so that one end is plugged and the other end is open.

[0132] (6) The green product is sintered in an inert atmosphere at a protective atmosphere temperature of 1400-1700°C.

[0133] Comparative Example 2 (1) A uniform mixed powder having a close packing is prepared by dry mixing 81.26% by weight of 56-58 μm silicon carbide powder, 3.74% by weight of 0.35-0.65 μm ultrafine SiC powder, 15% by weight of 0.35-0.65 μm pre-oxidized bentonite, 48% by weight of a foaming resin as a pore former, and 7.5% by weight of an organic binder.

[0134] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material. The binder is hydroxypropyl methylcellulose and the pore-forming agent is foaming resin.

[0135] (2) The mixed powder is placed in a kneading machine. Based on the mass of the mixed powder being 100%, 21% by weight of water is added and the mixture is kneaded for 7 minutes. 3% by weight of an additive is added and the mixture is kneaded for 10 minutes. The additive can increase the plasticity, lubricity and surface activity of the mud. In this comparative example, potassium laurate and butter are added in a ratio of 1:1.

[0136] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0137] (4) In this comparative example, the plastic clay segment was extruded into a honeycomb structure, and a green body with a size of 40×40×177.8 mm was extruded with an outer skin, and then microwaved and dried.

[0138] (5) The dried green body is cut into fixed heights and then sintered at 1400°C in an oxidizing atmosphere.

[0139] Comparative Example 3 like Figure 2 As shown, the preparation process of the clinker powder in this comparative example is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 4 hours. After ball milling, the powder with a mesh size of 400-500 is sieved. After testing, the particle size D of the powder is 50 10-30μm, particle size D 100 Less than 100μm.

[0140] The clinker of this comparative example is sintered in an oxidizing atmosphere. The main crystal phases of the clinker and raw material of this comparative example are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0141] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0142] The preparation process of the thin-walled porous ceramic material of this comparative example is as follows: (1) 50% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore former, and 10% by weight of an organic binder are mixed by a dry method to obtain a densely packed and uniform mixed powder.

[0143] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0144] (2) The mixed powder is placed in a kneading machine, and then 50% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total weight of the mixed powder and the raw meal being 100%, the weight percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the weight percentage of water is 6%.

[0145] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0146] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0147] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0148] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0149] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0150] (7) Detect the properties of the prepared porous ceramic materials.

[0151] Comparative Example 4 like Figure 2 As shown, the preparation process of the clinker powder in this comparative example is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 20-24 hours. After ball milling, the powder is sieved to obtain a powder with a mesh size of 800-1000. After testing, the particle size D of the powder is 50 5-10μm, particle size D 100 Less than 100μm.

[0152] The clinker of this comparative example is sintered in a reducing atmosphere and a protective atmosphere. The main crystal phases of the clinker and the raw material of this comparative example are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0153] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0154] The preparation process of the thin-walled porous ceramic material of this comparative example is as follows: (1) 40% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore-forming agent, and 10% by weight of an organic binder are mixed by a dry method to obtain a densely packed and uniform mixed powder.

[0155] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0156] (2) The mixed powder is placed in a kneading machine, and then 60% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total weight of the mixed powder and the raw meal being 100%, the weight percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the weight percentage of water is 5%.

[0157] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0158] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0159] (4) The slurry was placed in a high-pressure hydraulic screening machine at 20 MPa, and the sieves of 100 mesh, 120 mesh, and 150 mesh were used to screen the slurry to remove coarse particles with a particle size greater than 100 μm. The experimental results of the screening and extrusion molding processes were similar to those in Example 3, and no molding could be achieved.

[0160] Comparative Example 5 like Figure 2 As shown, the preparation process of the clinker powder in this comparative example is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 2 hours. After ball milling, the powder with a mesh size of 300-400 is sieved. After testing, the particle size D of the powder is 50 5-10μm, particle size D 100 Less than 100μm.

[0161] The clinker of this comparative example is sintered in a reducing atmosphere and a protective atmosphere. The main crystal phases of the clinker and the raw material of this comparative example are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0162] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0163] The preparation process of the thin-walled porous ceramic material of this comparative example is as follows: (1) 40% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore-forming agent, and 10% by weight of an organic binder are mixed by a dry method to obtain a densely packed and uniform mixed powder.

[0164] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0165] (2) The mixed powder is placed in a kneading machine, and then 60% by weight of a raw meal of known composition is added, and at the same time, a waste oil-water mixture is added as a lubricant, and then water is added, and kneaded to obtain a slurry. Wherein, based on the total mass of the mixed powder and the raw meal being 100%, the mass percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the mass percentage of water is 6.5%.

[0166] Wet kneading is performed for 10 minutes, and then butter is added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this embodiment, 0.5% by weight of butter is added so that the mass ratio of the waste oil-water mixture to the butter is 28:1, which can achieve the purpose of further reducing costs.

[0167] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0168] (4) Place the slurry into segments on a 20 MPa high-pressure hydraulic screening machine and use 100 mesh, 120 mesh, and 150 mesh screens to screen the segments to remove coarse particles with a particle size greater than 100 μm.

[0169] (5) The plastic clay segment is extruded into a honeycomb structure, and a green body with a size of 38.5×38.5×203.2 mm is extruded with an outer skin, and then microwaved and dried.

[0170] (6) The dried green body is re-sintered in the original reducing atmosphere protective atmosphere.

[0171] (7) Detect the properties of the prepared porous ceramic materials.

[0172] Comparative Example 6 like Figure 2As shown, the preparation process of the clinker powder in this comparative example is to first cut the clinker in the obtained silicon carbide honeycomb ceramic waste, and then ball mill the cut clinker for 4 hours. After ball milling, the powder with a mesh size of 400-500 is sieved. After testing, the particle size D of the powder is 50 10-30μm, particle size D 100 Less than 100μm.

[0173] The clinker of this comparative example is sintered in a reducing atmosphere. The main crystalline phases of the clinker and raw material of this example are 50-70% silicon carbide, 15-20% metallic silicon, and 10-20% silicon dioxide.

[0174] After surface modification treatment with a mixture of a silane coupling agent and PEI, a clinker powder is obtained.

[0175] The preparation process of the thin-walled porous ceramic material of this comparative example is as follows: (1) 100% of the above-mentioned clinker powder, 8% by weight of alumina powder, 8% by weight of inorganic gel powder, 38% by weight of polymethyl methacrylate as a pore former, and 10% by weight of an organic binder are mixed by a dry method to prepare a mixed powder having a dense and uniform appearance.

[0176] The amount of pore-forming agent and organic binder added is based on the total amount of clinker and raw material, the binder is PVA, and the pore-forming agent is polymethyl methacrylate.

[0177] (2) The mixed powder is placed in a kneading machine, and then the waste oil-water mixture is added as a lubricant, and then water is added and kneaded to obtain a slurry. Wherein, based on the total mass of the mixed powder being 100%, the mass percentage of the waste oil-water mixture of 14% by weight of the total powder is 14%, and the mass percentage of water is 6%.

[0178] Wet kneading was performed for 10 minutes, and then butter was added as an organic lubricating dispersant according to the material properties of the mud material to further optimize the material properties of the mud material. In this comparative example, 0.5% by weight of butter was added so that the mass ratio of the waste oil-water mixture to the butter was 28:1.

[0179] (3) The clay material kneaded in step (2) is cut into clay segments, and then sliced ​​three times into segments.

[0180] (4) The slurry was placed in a high-pressure hydraulic screening machine at 20 MPa, and the sieves of 100 mesh, 120 mesh, and 150 mesh were used to screen the slurry to remove coarse particles with a particle size greater than 100 μm. During the experiment, the sieves of 120 mesh and 150 mesh were damaged. When the next step of extrusion molding was carried out, the slurry could not produce a honeycomb ceramic material with a fixed shape and could not be formed.

[0181] In order to verify the stability of the ceramic material of the present invention during use, the ceramic materials prepared in the above embodiments and comparative examples are subjected to the same or even more stringent characterization methods as the National VI stage silicon carbide honeycomb ceramic materials to verify the applicability of the ceramic products to the National VII emission regulations. Among the specific qualified conditions, the antioxidant performance test temperature and holding time are revised from 1400℃ / 100H to 1500℃ / 100H. At the same time, the softening temperature of the material is tested to examine whether it can fully meet the working conditions less than or equal to 1500℃.

[0182] Table 1 shows the key formulas of the above-mentioned embodiments and comparative examples. Table 2 shows the test results of the embodiments and comparative examples.

[0183] Table 1 Table 2 Table 3 shows the burning loss rates of the ceramic materials of Example 4, Example 6, Comparative Example 1 and Comparative Example 2 before and after 1500°C / 100H burning. Figure 6 This is a SEM comparison picture of the ceramic material of Example 4 before and after calcination.

[0184] Table 3 In order to compare the pressure drop of the embodiment, Examples 4 and 6 also prepared samples with a diameter of 304.8 mm, a height of 254 mm, a pore density of 600 cpsi, and a wall thickness of 4 mil. Of course, the diameter, height, pore density, and wall thickness of the material are not limited to these. The SEM micrograph of the surface of the thin-walled porous ceramic material in Example 4 is shown in FIG. Figure 3 As shown, the SEM micrograph of the wall surface of the thin-walled porous ceramic material in Example 4 is as follows Figure 4 shown.

[0185] The above test results are analyzed as follows: By comparing Examples 1-2 and 3-4, it can be seen that the wrapping of the clinker waste with the raw material waste can effectively increase the softening temperature of the product, indicating that the re-firing of the green waste does not reduce the heat resistance of the ceramic product. At the same time, the addition of clinker waste and the effective wrapping have no effect on the heat resistance of the ceramic product, further verifying the feasibility of the disclosed embodiments of the present invention. It can be further inferred that the raw material waste has no effect on the re-firing of the ceramic product, which can assist in verifying the attached Figure 5 Process feasibility of porous thin-walled ceramic products.

[0186] By comparing Example 4 and Example 6, it can be seen that the raw material waste and clinker waste used in the present invention, whether sintered in a protective atmosphere or an oxidizing atmosphere, can meet the requirements of the present invention for low cost of ceramic products and efficient utilization of solid waste.

[0187] By comparing Example 4 and Example 6 with Comparative Examples 1-2, it can be seen that the performance of the ceramic products obtained by using the waste oil-water mixture and the normal process flow without using the waste oil-water mixture are similar and can meet the requirements of use, further achieving the goal of reducing costs and increasing efficiency.

[0188] By comparing the experiments of Example 4 and Comparative Examples 4-5, it can be seen that when the particle size is too large, the extrusion cannot be formed and cannot meet the requirements of preparing thin-walled porous materials. When the particle size is too small, it can meet the requirements of preparing thin-walled porous materials, but the preparation cost of the clinker powder is increased, which cannot meet the innovative requirements of low cost and high efficiency of this patent. Therefore, it can be confirmed that the optimal particle size range is 10-30μm.

[0189] When comparing Examples 3-5 and Comparative Example 6, it can be seen that adding all raw waste or adding more raw waste has better heat resistance than adding all clinker waste or adding more clinker waste. When 100% clinker is used, extrusion molding is impossible. From the perspective of reducing costs, adding more clinker waste is less expensive, which is related to the ratio of raw material and clinker solid waste generated in the production stage of ceramic products. In general, the ratio of clinker waste generated in the production process is much higher than the ratio of raw material waste. Comparing the experimental results and the actual amount of solid waste generated, it is preferred to add more clinker solid waste while ensuring that the softening temperature of the product is greater than 1780°C.

[0190] Therefore, the present invention uses a method similar to that of Example 4 and Example 6, uses a large amount of solid and liquid waste generated during the production process, reduces production costs, and prepares a porous, thin-walled ceramic material with a porosity greater than 60% and a median pore size of 21-23 μm. Including but not limited to the field of honeycomb ceramic filters, other impurity gas filters, etc., all belong to the scope of protection of the present invention.

[0191] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a thin-walled porous ceramic material, characterized in that: Prepared by using silicon carbide honeycomb ceramic waste; the silicon carbide honeycomb ceramic waste includes clinker and / or raw material, the clinker is waste material that has been sintered but not cold processed, and the raw material is waste material that has not been sintered; The preparation method comprises the step of pre-treating the clinker and / or the raw material, wherein the pre-treating step comprises ball milling-sieving and surface modification of the clinker to obtain clinker powder; the particle size of the clinker powder is D 50 10-30μm, particle size D 100 Less than 100μm.

2. The method for preparing a thin-walled porous ceramic material according to claim 1, characterized in that: The pretreatment step also includes dissolving the raw material in water.

3. The method for preparing a thin-walled porous ceramic material according to claim 1, characterized in that: The sintering method of the clinker includes sintering in a reducing protective atmosphere or sintering in an oxidizing atmosphere.

4. The method for preparing a thin-walled porous ceramic material according to claim 1, characterized in that: The surface modification treatment is a chemical coating modification treatment using a chemical modifier, and the chemical modifier is one or more of an organic silane coupling agent, a titanate coupling agent, an aluminate coupling agent, an organic complex, organic silicon, and PEI.

5. A method for preparing a thin-walled porous ceramic material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, pre-treating the clinker and / or the raw material; S2, obtaining a first mixed powder or a second mixed powder, wherein the first mixed powder is a mixture of alumina powder, inorganic gel powder, pore former, organic binder and the pretreated clinker, and the second mixed powder is a mixture of alumina powder, inorganic gel powder, pore former and organic binder; S3, mixing the first mixed powder with the pretreated raw material to obtain a kneading material, or mixing the second mixed powder with the pretreated raw material to obtain a kneading material; wet kneading the kneading material with a lubricant and water to obtain a mud material; the lubricant includes a waste oil-water mixture and / or an organic lubricating dispersant; S4, preparing and cutting the clay material to obtain clay segments; S5, removing coarse particles with a particle size greater than 100 μm in the mud section, and then performing extrusion molding, microwave, drying and sintering to obtain the thin-walled porous ceramic material.

6. The method for preparing a thin-walled porous ceramic material according to claim 5, characterized in that: In step S2, based on the total mass of the clinker and the raw material as 100%, the mass percentage of the alumina powder is 7%-9%, the mass percentage of the inorganic gel powder is 7%-9%, the mass percentage of the pore former is 36%-40%, and the mass percentage of the organic binder is 8%-12%.

7. The method for preparing a thin-walled porous ceramic material according to claim 6, characterized in that: The organic binder is one or more of cellulose, polyvinyl alcohol, and nylon plastics, and the pore-forming agent is one or more of starch pore-forming agent, polymethyl methacrylate, and resin pore-forming agent.

8. The method for preparing a thin-walled porous ceramic material according to claim 5, characterized in that: In step S3, based on the total mass of the kneaded material being 100%, the mass percentage of the lubricant is 13%-15%, and the mass percentage of water is 4%-8%.

9. The method for preparing a thin-walled porous ceramic material according to claim 5, characterized in that: In step S5, the sintering method is consistent with the sintering method of the clinker.

10. A thin-walled porous ceramic material, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Large-size thin-wall cordierite honeycomb ceramics carrier mud and preparation method thereof

    CN105503233A

  • Method for manufacturing honeycomb structure containing silicon carbide

    CN113443914A

  • Honeycomb ceramic carrier for purifying VOCs with high thermal shock as well as preparation method and application of honeycomb ceramic carrier

    CN117164353A

  • Preparation method of gradient porous silicon carbide ceramic

    CN117756549A

  • DEVELOPMENT OF CERAMIC MATERIALS MADE FROM REFRACTORY WASTE FOR HIGH-TEMPERATURE THERMAL ENERGY STORAGE APPLICATIONS

    FR3105975A1